PEMBUATAN APLIKASI WEBSITE UNTUK PENYUSUNAN MATERI PELAJARAN SECARA ONLINE - Fujianto -; Agustinus Noertjahyana; Andreas Handojo (Jurnal Infra, 2014)
The development of technology, especially the Internet makes information services evolved. With the internet, information can be easily shared and accessed by many people . These developments have broad impact on all sectors , including in the field of education . The use of the Internet can be used as a container for distributing information better lesson.Applications developed using HTML5 with the help of jquery to display on a web browser on a desktop or web browser table . Meanwhile, to beautify the appearance of the website can also use javascript and CSS3 . As for data storage to be able to use a MySql database.Applications website for breastfeeding online course material is used to make subject matter accessible to many people. In addition, by making the delivery of better material information with the video.